التخييل من منظور الفلاسفة المسلمين - حفحوف,سميرة; قحام,توفيق (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى معالجة أهم نظرية جعلت من نفسها رُكنا من أركان بناء الأقاويل الشعرية ألا وهي نظرية التخييل، التي تمخضت من رحم التزاوج بين المعرفة اليونانية والعربية، كون هذه النظرية تُمثل جوهر الصناعة الشعرية، الأمر الذي ركَّز عليه فلاسفة الإسلام في أبحاثهم ودراساتهم على وجه أخص أبو نصر محمد الفارابي، وعليه سنحاول من خلال هذه الدراسة الوقوف على آراءه النقدية تجاه هذه النظرية. Abstract: The present study aims to address the most important theory that has made itself a pillar of the construction of poetic sayings, which is the theory of imagination, that emerged from the integration between Greek and Arabic knowledge since this theory represents the essence of the poetic industry, which is what Islamic philosophers focused on in their research and studies in particular Abu Nasr Muhammad al-Farabi. Therefore we will try through this study to find out his critical opinions regarding this theory. So, we have reached: - Imagination represents the foundation upon which poetic statements are built, just like the pillars of poetry; -Greek knowledge in general and Aristotelian knowledge in particular had a great influence on Arab-Islamic culture, which was clearly demonstrated through what Al-Farabi presented in his studies.
أبو نصر محمد الفارابي أنموذجا
Keywords: الفارابي; الأقاويل الشعرية; المعرفة اليونانية; الثقافة العربية; Al-Farabi; imagination; poetic sayings; Greek knowledge; Arab culture